Human Behavior in the Digital Age: Study of Social Media Users’ Behavior and Its Impact on Mental and Physical Health in the Future - Lydia Irene Siahaan; Magdalena Hanoum; Muhammad Syukur; Asriani Alimuddin; Lumastari Ajeng Wijayanti (Global Writing Academica Researching & Publishing, 2023)
Technological developments present various new things in human life, including social media. Behavior in using social media can affect the lives of its users. Often the negative behavior that is carried out when using social media has an impact on mental and physical health. This study then aims to see how social media usage behavior impacts mental and physical health in the future. This research is descriptive qualitative research. The data used in this study comes from various research results and previous studies. The results of this study indicate that excessive use of social media can have addictive effects. This addiction can impact mental health through depression, stress, anxiety, and loneliness. If this mental health disorder occurs for a long time, it will cause physical disturbances such as changes in blood pressure and hypertension. In addition, excessive use of social media can also cause problems with eye health and sleep problems.